(untitled) (mathematica didactica, 2020)
Mathematics trails are currently experiencing a renaissance as an extracurricular form of learning for mathematics lessons. Learning arrangements in which students work on mathematics tasks outdoors allow for various context-related modelling activities if the tasks are designed accordingly. Especially when mathematics trails are supported by digital media, there are possibilities and potentials for the promotion of mathematics learning. So far, how-ever, mathematics trails are not yet sufficiently didactically described. In the article three central didactic perspectives on mathematics trails - extracurricular learning, support with digital media and mathematical modelling - are theoretically discussed and concretized with regard to the implementation of trails.